Contribution of deaths of despair to the Hispanic mortality advantage in the USA by person, place and time: an ecological analysis of vital registration data - Usama Bilal; Mariana Lazo; Bricia Gonzalez Trejo; Stephanie M Hernandez (BMJ Publishing Group, 2024)
Introduction In the USA, Hispanics exhibit longer life expectancy (LE) compared to non-Hispanic whites despite facing greater socioeconomic adversity and greater health risk factors, a phenomenon known as the Hispanic paradox. With recent increases in mortality due to 'deaths of despair' among non-Hispanic whites and other groups it is important to understand the contribution of deaths of despair to the Hispanic mortality advantage overall and how it varies by age and geography.Methods Using national mortality data across three decades (1990-2019) we calculated LE at birth for Hispanics and non-Hispanic whites, overall and by place (established Hispanic destinations before 1990, and new Hispanic destinations by 2000, 2010 and 2020). We used the Arriaga method to decompose the contribution of deaths of despair to the Hispanic mortality advantage by age, time and place.Results The Hispanic mortality advantage has progressively increased over time for both females and males. For females 15-39 years of age, the contribution of deaths of despair to a Hispanic mortality advantage rose from 0.02 years in 1990-1994 to 0.25 years in 2015-2019. For males, the contribution changed from 0.02 years to 0.50 years in the same period. The contribution of deaths of despair to the Hispanic mortality advantage appears smaller in established destinations, potentially plateauing for younger individuals, while presenting a marginal Hispanic disadvantage among older individuals in these areas.Conclusion Despite persistent socioeconomic disadvantages, US Hispanics have continuously held higher LE compared to non-Hispanic whites since 1990. Among other causes, this advantage reflects the sustained increase of deaths of despair in contributing to the Hispanic mortality advantage, but its significance varies across geography with lower contributions in established Hispanic destinations.